1998
DOI: 10.1111/j.1468-3083.1998.tb00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergens in patients with leg ulcers

Abstract: The changing trends in contact allergens over the last 20 years may be explained by changes in the components of topical agents used for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 7 publications
2
13
0
1
Order By: Relevance
“…It seems as though the treatment of chronic leg ulcer/stasis dermatitis could have improved from the allergological point of view: fewer patients are sensitized by topical preparations, and/or they are patch tested earlier. This may be interpreted as a sign of increasing awareness of this issue among healthcare professionals and patients with chronic wounds, and is in concordance with trends in other countries . However, patch testing of routine substances included in established test series will not identify new allergens (e.g.…”
Section: Discussionsupporting
confidence: 58%
“…It seems as though the treatment of chronic leg ulcer/stasis dermatitis could have improved from the allergological point of view: fewer patients are sensitized by topical preparations, and/or they are patch tested earlier. This may be interpreted as a sign of increasing awareness of this issue among healthcare professionals and patients with chronic wounds, and is in concordance with trends in other countries . However, patch testing of routine substances included in established test series will not identify new allergens (e.g.…”
Section: Discussionsupporting
confidence: 58%
“…Our analysis focuses on a potential side‐effect of topical antimicrobial therapy—the risk of sensitization against the active ingredient. This is a well‐known sequel of topical treatment of stasis dermatitis and varicose ulcer, be it with antimicrobials, or virtually any substance applied topically 18,19 . As in stasis dermatitis, the epidermal barrier is often (severely) impaired in clinically active atopic eczema, which can be expected to promote sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of allergens involved in allergic contact dermatitis affecting the skin around venous leg ulcers appears to be changing, and this change is likely to be determined by local wound‐care practice. Studies published within the past 10 years have suggested an increasing frequency of rubber accelerator allergy (10), compared to earlier studies which highlighted aminoglycoside antibiotics, balsam of Peru (Myroxylon Pereirae resin) and lanolin alcohol as among the most frequent allergens in patients with venous hypertension and leg ulcers (6, 11–13). Another recent study showed a high frequency (4/36; 11%) of patients with venous insufficiency to have apparently allergic patch test reactions to hydrogels (3).…”
mentioning
confidence: 99%